Análise do potencial turístico agroindustrial familiar rural: implantação de rotas - Luz, Jéssica Becker da (2020)
The objective of this work was to analyse the Family agribusinesses participating in the Project Development of Regional Rural Tourism in the West of Paraná, located in the municipality of Cascavel/PR as propellers of sustainable rural development through rural tourism. The Cascavel food production can represent a potential for the rural tourism promotion in the region. For this, the metodhological guidance was based on bibliographic research. Regarding the approach it is a descriptive character with a qualitative focus. As for the objectives, this research is characterized as a study of multiple cases seeking to highlight the unique characteristics of each property addressed being carried out the data survey through interviews with the objective of familiarizing the studied problem. Results: The properties evidenced by the study can receive visitors so that the development of rural tourism can bring sustainable development, generating income, employment, empowerment, and other factors. In addition, there is the possibility of creating rural tourism routes linked to the municipal Family agribusiness.